1994
DOI: 10.1111/j.1151-2916.1994.tb04641.x
|View full text |Cite
|
Sign up to set email alerts
|

Hardness–Grain‐Size Relations in Ceramics

Abstract: Both Vickers and Knoop hardness ( H ) , measured at two or more loads in the range of 100-2000 g (most commonly 100 and 500 g) for a variety of dense oxide and non-oxide materials, covering a range of grain sizes (G), including single crystals where possible, were shown to generally be consistent with (often more limited) literature data. Apparently, conflicting trends of H (1) showing either no G dependence, (2) decreasing from single-crystal or large G values with decreasing G, or (3) having the generally ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
120
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(135 citation statements)
references
References 40 publications
12
120
2
1
Order By: Relevance
“…For example, the hardness is an essential prerequisite of evaluating the fracture toughness of ceramic materials [14]. The utility of hardness is further enhanced by the fact that it is obtained by a simple indentation test that can be rapidly performed on relatively small samples at moderate cost [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the hardness is an essential prerequisite of evaluating the fracture toughness of ceramic materials [14]. The utility of hardness is further enhanced by the fact that it is obtained by a simple indentation test that can be rapidly performed on relatively small samples at moderate cost [15].…”
mentioning
confidence: 99%
“…As for some ceramic materials, grain orientation [16] and chemical decomposition [17] also affect hardness. From the literature, the dependence of hardness on grain size does not always show a single trend that applies to every ceramic material [15], as suggested by Rice et al who have reviewed the relationship between grain size and hardness of a variety of oxides and non-oxide ceramics [15]. For example, studies on ceramic materials including MgO, BeO, Al 2 O 3 , MgAl 2 O 4 and B 4 C [15] as well as hydoxyapatite [18] have shown that an increase in grain size leads to a decrease in hardness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Use of nanograin ceramics can also improve sinterability due to the higher surface area, and resultant nano scale grains can enhance mechanical reliability by reducing the critical flaw size. The high volume fraction of grain boundaries in nano grain compacts can increase fracture toughness as well as other mechanical properties [10]. The sintering temperature of nano-HA with the addition of Ti was studied by microwaves synthesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hardness of a material depends upon several parameters, including grain size, indenter load and loading rate, indenter geometry, surrounding environment, and accuracy in measurements [1][2][3]. Generally, hardness decreases with the increase of indenter load and indentation size, known as indentation size effect (ISE) [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%